PENERAPAN MODEL PEMBELAJARAN CIRCUIT LEARNING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS X SMA N 1 PASIR PENYU - Ramadhani Fitri; Agusfitriani Agusfitriani (Universitas Islam Sumatera Utara, 2018)
Abstract. This study aims to determine students' mathematical communication skills using the Circuit Learning learning model. This research is a Quasi Experiment study with the design of the Randomized Subjects Posstest Only Control Group Design. The study population was all students of class X SMA N 1 Pasir Penyu. The sampling technique uses random sampling. The instrument used was a mathematical communication ability test in the form of a description. Data were analyzed statistically by the Independent Samples T-Test. Based on the results of the t test, tcount in the rejection area of H0 can be concluded that the mathematical communication skills of students taught with the circuit learning learning model are better than conventional learning.Keywords: Mathematical Communication, Circuit Learning.